2005
DOI: 10.1128/jvi.79.15.9527-9539.2005
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T-Cell Reconstitution Reduces Cytomegalovirus in the Immunocompromised Brain

Abstract: Cytomegalovirus (CMV) infection is the most common opportunistic infection of the central nervous systemin patients with human immunodeficiency virus or AIDS or on immunosuppressive drug therapy. Despite medical management, infection may be refractory to treatment and continues to cause significant morbidity and mortality. We investigated adoptive transfer as an approach to treat and prevent neurotropic CMV infection in an adult immunodeficient mouse model. SCID mice were challenged with intracranial murine CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…A similar study reported that murine CMV-specific immune cells, particularly CD4+ T-cells, rapidly cross the blood-brain barrier, congregate at sites of specific MCMV infection, and eliminate acute MCMV within the brain (Reuter et al , 2005). These studies suggest that infiltrating T-cells clear viral brain infection potentially through an MHC dependent, perforin-mediated cytotoxic T lymphocyte (CTL) response.…”
Section: Discussionmentioning
confidence: 97%
“…A similar study reported that murine CMV-specific immune cells, particularly CD4+ T-cells, rapidly cross the blood-brain barrier, congregate at sites of specific MCMV infection, and eliminate acute MCMV within the brain (Reuter et al , 2005). These studies suggest that infiltrating T-cells clear viral brain infection potentially through an MHC dependent, perforin-mediated cytotoxic T lymphocyte (CTL) response.…”
Section: Discussionmentioning
confidence: 97%
“…The adult brain is protected from CMV by a number of mechanisms, including a CD4 (39) and peripheral CD8 (36) T-cell response. We have previously shown that developing brain cells in vivo and in vitro are more likely to show mCMV infections than mature brain cells, and that this preference is independent of the host B-and T-cell responses (57,61).…”
Section: Discussionmentioning
confidence: 99%
“…Later studies using the same murine system also demonstrated that controlling CMV mediated lung disease in treated mice required CD8+ T cells rather than CD4+ T cells (Steffens et al, 1998;Podlech et al, 2000). However, when adoptive transfer was performed in severe combined immunodeficiency (SCID) mice, CD4+ T cells were able to prevent viral dissemination in the brain (Reuter et al, 2005). Overall, therefore, CD4+ T cells appear to be essential only for control of viral replication in the specific organs in the mouse model.…”
Section: Approaches To Examining the Role Of Cd4+ T Cells In MCMV Infmentioning
confidence: 99%